Politics and economics : papers in political economy - Robbins, Lord. (London : Macmillan ; New York : St Martin's Press, 1963)
The papers in this collection fall into three divisions. The first consists of a single paper, "On the Relations between Politics and Economics", The second division comprises six papers which are concerned with the general theory of the state and relations between state, with special reference to the principles of economic policy. The third division consists of three papers of a rather more technical nature, concerned with problems of high finance.
Includes bibliographical footnotes and index.
rpm 26/09/2017
Loans
Keywords: Economics